Adenomyosis and Infertility (Bangladesh Journal of Obstetrics & Gynaecology, 2019)
Adenomyosis is an abnormal growth of endometrial glands and stroma into the myometrium causing diffusely enlarged uterus. Due to the abnormal growth of endometrial glands and stroma it causes severe pain during menstruation. Though USG and MRI can help, histopathology of the lesion is confirmatory diagnosis of the disease. It is one of the important causes of infertility with very poor prognosis. Any treatment modalities can fail when lesion is diffuse in nature. Surgery in the form of total hysterectomy is the definitive treatment for complete cure but hysterectomy is not logical for infertile patients. So, fertility sparing surgery can be done to improve fertility. Medical treatment in the form of GnRHa and different form of progesterones can be used to eliminate symptoms and to reduce the adenomyotic mass, which may improve the fertility status. Non-surgical High Intensity Focused Ultrasound (HIFU) is another option to reduce the size of the lesion. For reproduction active treatment is ideal to accelerate live birth. Controled ovarian hyperstimulation and Intrauterine Insemination (IUI) can be done if tube(s) are patent. If not, Assisted Reproductive Technology (ART) is the treatment of choice for this group of patients.Bangladesh J Obstet Gynaecol, 2019; Vol. 34(2): 112-123